DAMPAK COVID-19 TERHADAP PERUBAHAN FERTILITAS DI INDONESIA - MUHAMMAD ARIF FAHRUDIN ALFANA (JURNAL GEOGRAFI, 2021)
The Covid-19 pandemic has impacted various demographic parameters in Indonesia. One of the parameters affected is fertility. This study discusses the impact of Covid-19 on changes in fertility parameters in Indonesia. The parameters measured were the number of pregnancies, the number of births, the number of Total Fertility Rate (TFR) and the number of people 0-4 years. This study uses a quantitative approach, with secondary data analysis methods. Data processing in this study using spectrum software. The modules used in the software are DemProj and FamPlan. The basic assumption made in this study is the decline in users of short-term contraceptive methods (condoms, pills, and injections) during the Covid-19 pandemic. The results showed that Covid-19 has the potential to have an impact on increasing the number of pregnancies, increasing the number of births, increasing the TFR rate and increasing the number of Indonesians aged 0-4 years.